Comparison of oncological outcomes after open and laparoscopic re‐resection of incidental gallbladder cancer. Issue 3 (24th December 2019) - Vega, E. A.; De Aretxabala, X.; Qiao, W.; Newhook, T. E.; Okuno, M.; Castillo, F.; Sanhueza, M.; Diaz, C.; Cavada, G.; Jarufe, N.; Munoz, C.; Rencoret, G.; et al.
Abstract : Background: The safety and oncological efficacy of laparoscopic re‐resection of incidental gallbladder cancer have not been studied. This study aimed to compare laparoscopic with open re‐resection of incidentally discovered gallbladder cancer while minimizing selection bias. Methods: This was a multicentre retrospective observational cohort study of patients with incidental gallbladder cancer who underwent re‐resection with curative intent at four centres between 2000 and 2017. Overall survival (OS) and recurrence‐free survival (RFS) were analysed by intention to treat. Inverse probability of surgery treatment weighting using propensity scoring was undertaken. Results: A total of 255 patients underwent re‐resection (190 open, 65 laparoscopic). Nineteen laparoscopic procedures were converted to open operation. Surgery before 2011 was the only factor associated with conversion. Duration of hospital stay was shorter after laparoscopic re‐resection (median 4 versus 6 days; P  < 0·001). Three‐year OS rates for laparoscopic and open re‐resection were 87 and 62 per cent respectively ( P  = 0·502). Independent predictors of worse OS were residual cancer found at re‐resection (hazard ratio (HR) 1·91, 95 per cent c.i. 1·17 to 3·11), blood loss of at least 500 ml (HR 1·83, 1·23 to 2·74) and at least four positive nodes (HR 3·11, 1·46 to 6·65). In competing‐risks analysis, the RFS incidence was higher for laparoscopic re‐resection ( P  = 0·038), but OS did not differ between groups. Independent predictors of worse RFS were one to three positive nodes (HR 2·16, 1·29 to 3·60), at least four positive nodes (HR 4·39, 1·96 to 9·82) and residual cancer (HR 2·42, 1·46 to 4·00). Conclusion: Laparoscopic re‐resection for selected patients with incidental gallbladder cancer is oncologically non‐inferior to an open approach. Dissemination of advanced laparoscopic skills and timely referral of patients with incidental gallbladder cancer to specialized centres may allow more patients to benefit from this operation. Abstract : Oncological extended resection is the optimal treatment for resectable incidental gallbladder cancer. The outcomes of a multi‐institutional study of the safety and oncological efficacy of a laparoscopic approach are reported. Equal outcomes in selected patients Abstract : Antecedentes: No se conoce la seguridad y la eficacia oncológica de la re‐resección laparoscópica del cáncer incidental de vesícula biliar. Este estudio tiene como objetivo comparar las re‐resecciones del cáncer incidental de vesícula biliar por vía laparoscópica y vía abierta, minimizando el sesgo de selección. Métodos: Estudio de cohortes observacional, retrospectivo y multicéntrico de pacientes con cáncer incidental de vesícula biliar que se sometieron a una re‐resección con intención curativa en 4 centros entre 2000 y 2017. Se analizó la supervivencia global ( overall survival, OS) y la supervivencia libre de recidiva ( recurrence free survival, RFS) según intención de tratamiento. Se calculó la probabilidad inversa de la ponderación del tratamiento quirúrgico utilizando puntuación de propensión. Resultados: Se incluyeron 255 pacientes con re‐resección (190 por vía abierta y 65 por vía laparoscópica). Se convirtieron 19 pacientes del grupo laparoscópico. El único factor relacionado con la conversión fue la realización de la cirugía antes de año 2011. La mediana de la estancia hospitalaria fue más corta tras la re‐resección laparoscópica (4 versus 6 días; P < 0, 001). La OS a tres años fue del 87% y del 62% ( P = 0, 502) para las re‐resecciones laparoscópicas y abiertas, respectivamente). Los factores predictivos independientes relacionados con una peor OS fueron el hallazgo de cáncer residual en el momento de la re‐resección (cociente de riesgos instantáneos, hazard rati o, HR 1, 91; i.c. del 95% 1, 17‐3, 11), una pérdida hemática > 500 ml (HR 1, 83; i.c. del 95% 1, 23‐2, 74) y la presencia de ≥ 4 ganglios positivos (HR 3, 11; i.c. del 95% 1, 46‐6, 65). En el análisis de riesgo competitivo, la RFS fue mayor para la resección laparoscópica ( P = 0, 038), pero no hubo diferencias en la OS entre ambos grupos. Los factores predictivos independientes de peor RFS fueron la detección de 1‐3 ganglios positivos (HR 2, 16; i.c. del 95% 1, 29‐3, 60), ≥ 4 ganglio positivos (HR 4, 39; i.c. del 95% 1, 96‐9, 82) y el cáncer residual (HR 2, 42; i.c. de 95% 1, 46‐4, 0). Conclusión: En pacientes seleccionados, los resultados oncológicos de la re‐resección laparoscópica de un cáncer incidental de vesícula biliar no son inferiores a los que se obtienen por vía abierta. Una mayor difusión de las técnicas laparoscópicas avanzadas y una oportuna derivación de los pacientes con cáncer de vesícula biliar incidental a centros especializados podrían permitir que un mayor número de pacientes se beneficiaran de este abordaje.